Does size matter? Examining the effect of obesity on inpatient amputation rehabilitation outcomes. Issue 1 (2nd January 2017) - Vivas, Lilian L. Y.; Pauley, Tim; Dilkas, Steven; Devlin, Michael
Abstract: Purpose This study investigated whether obesity impacted clinical outcomes of patients at discharge from inpatient amputation rehabilitation.Method This was a retrospective chart review examining admissions for lower extremity amputation rehabilitation at a Canadian Regional Amputee Rehabilitation Programme between December 2011 and June 2014. Discharge outcomes were predefined as the two-minute walk test (2MWT), the L-test of functional mobility and the SIGAM score. These were compared between each body mass index (BMI) group (underweight   < 18.4 kg/m 2, normal between 18.5 and 24.9 kg/m 2, overweight between 25.0 and 29.9 kg/m 2 and obese greater or equal to 30 kg/m 2 ) as a whole and within transtibial, transfemoral and bilateral amputation groups.Results Of the 289 admissions meeting inclusion criteria, only underweight patients walked significantly less distance on the 2MWT than normal weight patients. There were group differences in the L-test, but post hoc testing was unable to qualify the differences. No significant difference was found in the SIGAM score. There were no significant differences found in the 2MWT, L-test or SIGAM when patients were grouped by amputation level.Conclusions Obesity does not appear to significantly impact inpatient amputation rehabilitation outcomes such as the 2MWT, L-test or SIGAM score. As such, obesity should not be a deciding factor as to whether a patient is offered rehabilitation. Implications for Rehabilitation: Obesity is increasing in prevalence and is comorbid with peripheral vascular disease and diabetes, the leading causes of lower extremity amputation. Function is compromised in the obese general population when compared to non-obese individuals. Obesity does not seem to confer a disadvantage with regards to validated outcomes, such as the 2-min walk test, L-test or SIGAM score at discharge after inpatient amputation rehabilitation. Obesity should not be a barrier to offering inpatient rehabilitation to amputation patients.